The metabolomics of psoriatic disease - Yan D (Dove Medical Press, 2017)
Di Yan, Ladan Afifi, Caleb Jeon, Megha Trivedi, Hsin Wen Chang, Kristina Lee, Wilson Liao Department of Dermatology, University of California-San Francisco, San Francisco, CA, USA Abstract: Metabolomics is an emerging new “omics” field involving the systematic analysis of the metabolites in a biologic system. These metabolites provide a molecular snapshot of cellular activity and are thus important for understanding the functional changes in metabolic pathways that drive disease. Recently, metabolomics has been used to study the local and systemic metabolic changes in psoriasis and its cardiometabolic comorbidities. Such studies have revealed novel insights into disease pathogenesis and suggest new biochemical signatures that may be used as a marker of psoriatic disease. This review will discuss common strategies in metabolomics analysis, current findings in the metabolomics of psoriasis, and emerging trends in psoriatic metabolomics. Keywords: metabolome, psoriasis, psoriatic arthritis, skin, urine, metabolites